Winners and Losers of Multinational Firm Entry into Developing Countries: Evidence from the Special Economic Zones of the People's Republic of China - Avraham Ebenstein (Asian Development Bank (ADB), 2011)
This paper examines the impact of multinational firm entry into local labor markets on employment, productivity, and wages. It exploits a natural experiment associated with the People's Republic of China's rapid economic reforms and assignment of cities to special economic zone status in the 1980s and 1990s. Using data on both firms and workers, it is found that these policies increased foreign direct investment, which raised average labor productivity in these labor markets. However, only modest increases in median wage rates across these cities are observed in the face of large increases in wage inequality and rising local prices, limiting the benefits to most workers in these cities. Evidence is presented that corporate profits captured most of the increase in productivity in these areas.
hdl:11540/1999
Keywords: 330; Sonderwirtschaftszone; Multinationales Unternehmen; China